2009
DOI: 10.1001/archoto.2009.70
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Postoperative Concurrent Chemoradiotherapy for Locally Advanced Major Salivary Gland Carcinoma

Abstract: Locally advanced or high-grade salivary gland carcinomas follow an aggressive clinical course. Based on our limited experience, postoperative chemoradiation with a platinum-based regimen seems to be effective in selected patients and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 17 publications
0
72
1
2
Order By: Relevance
“…In our study, the frequencies of distant metastasis in high-grade mucoepidermoid carcinoma, adenoid cystic carcinoma and salivary duct carcinoma were 40, 20 and 13%, respectively. A potential benefit in 3-year OS for adjuvant platinum-based CCRT compared with matched controls in 12 patients with major salivary gland carcinoma has been demonstrated in a small retrospective review (8). In addition, certain histologic types of parotid gland cancers also exhibit specific molecular targets for potential treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the frequencies of distant metastasis in high-grade mucoepidermoid carcinoma, adenoid cystic carcinoma and salivary duct carcinoma were 40, 20 and 13%, respectively. A potential benefit in 3-year OS for adjuvant platinum-based CCRT compared with matched controls in 12 patients with major salivary gland carcinoma has been demonstrated in a small retrospective review (8). In addition, certain histologic types of parotid gland cancers also exhibit specific molecular targets for potential treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancies of the salivary glands are estimated to comprise approximately 5% of all head and neck cancers and represent a wide array of pathologies due to the numerous cell types present in the salivary secretory acini and ductal units [1,2]. Adenocarcinoma (adenoCA) is estimated as the third most common malignancy of the salivary glands, after mucoepidermoid carcinoma and adenoid cystic carcinoma [1,3,4], but itself offers varying histologic subtypes, of which the most common are salivary ductal carcinoma (SDC), adenocarcinoma not otherwise specified (adenoCA NOS), salivary ductal carcinoma ex-pleomorphic adenoma (SDCA ex pleo), polymorphous type adenocarcinoma (PLGA), cystadenocarcinoma and basal cell adenocarcinoma (BCA).…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding survival rates were 49 and 19%, respectively (p = 0.015). More recently, a single institution report has suggested that combining radiation with platinum-based chemotherapy may improve long-term survival among patients with locally advanced salivary gland carcinoma [19] . Thus, this treatment approach warrants investigation in patients with salivary gland carcinoma and clinically obvious lymph node metastases.…”
Section: The Clinically Positive Neckmentioning
confidence: 99%
“…In many of these cases, the first echelon is represented by the intraparotid lymph nodes. The mean numbers of intraparotid lymph nodes that have been reported are 7 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in the superficial lobe and 2 (range, 0-9) in the deep lobe [38] . Furthermore, a statistically significant correlation (p = 0.005) has been observed between the presence of intraparotid metastatic nodes and neck node metastases [39] .…”
Section: Sentinel Node Biopsy In Primary Parotid Cancermentioning
confidence: 99%